CHARACTERISATION OF CALCAREOUS SOILS IN RANGAREDDY DISTRICT OF TELANGANA STATE - S. TRIVENI; D. SRINIVASA CHARY, MERAJ SIDDIQUA, S. HARISH KUMAR SHARMA, M. SHANKARIAH (The Journal of Research, PJTSAU, 2023)
A survey was conducted in the year 2019-20 in old Rangareddy district of Telangana state to study the characters of calcareous soils, based on effervescence with dil.HCL the samples were collected and were analysed for its characters. Majority of soils collected were medium to high in CaCO3 status. All the soils collected were alkaline to highly alkaline in reaction. Soils were low to medium in available nitrogen and phosphorus content. The average pH, available N, available P2O5, available K2O value recorded in these soils were 8.49, 77.19 Kg ha-1, 6.215 Kg ha-1, 72.88 Kg ha-1 respectively. Correlation study reported that there is significant positive relationship is seen between CaCO3 content and pH and significant negative relationship is seen between CaCO3 content and available N and P2O5 in soil. No significant relationship is seen between CaCO3 content and EC and OC values and significant positive relationship is seen with available K.